Global outlook for ice & snow - Eamer, Joan; Ahlenius, Hugo; Prestrud, Pål (Division of Early Warning and Assessment (DEWA), United Nations Environmental Programme, 2007)
Global Outlook for Ice and Snow provides an up-to-date, concise review of the state of the environment and the trends in ice and snow-covered regions (cryosphere) of the world. It features case studies, illustrations, graphics and maps and serves as an educational and reference publication. With a broad target audience that includes decision-makers at many levels, the report looks at the significance of changes in the cryosphere to human well-being and the implications for policy.